Auditory brainstem implants (ABIs) – 20 years of clinical experience in Uppsala, Sweden. (October 2014) - Siegbahn, Malin; Lundin, Karin; Olsson, Gun-Britt; Stillesjö, Fredrik; Kinnefors, Anders; Rask-Andersen, Helge; Nyberg, Gunnar
Abstract Conclusions: Even though sound perception may be limited after treatment with an auditory brainstem implant (ABI), it provides benefits and should be selectively offered to patients. Importantly the patients must be motivated, given reasonable expectations of outcome and offered long-term rehabilitation with a considerable 'learn to listen' period with the implant device. Objectives: To describe the clinical experiences and results of 24 ABI surgeries performed in Uppsala University Hospital between 1993 and 2013. Methods: Most patients (n = 20) suffered from neurofibromatosis type 2 (NF2); a few patients (n = 4) were paediatric non-NF2 patients. The files were searched for information on the presurgery size of the vestibular schwannoma, whether the patient had undergone gamma knife treatment, the surgical approach, the side effects of the surgery and of the use of the implant, the electrode activation pattern and implant use, and categories of auditory performance (CAP) score. Results: Our results show that many patients greatly benefited from an ABI, and most of the patients used their implants even though the hearing improvements usually consisted of awareness of surrounding sounds and improved lip-reading. No severe side effects were observed from implant stimulation.